Pembentukan Karakter Generasi Muda Yang Berakhlak Islami ala Manajemen Pendidikan Pesantren - Annisya, Susanti Mutiara; Gery Resty, Galuh (Pascasarjana Universitas Al-Qolam Malang, 2025)
Character building in the younger generation is crucial for its revival. The younger generation is the spearhead and main pillar for the future revival of the ummah. The young generation must be nurtured with noble morals so that they can support and deliver the message of Islam. Pesantren, as a typical Indonesian Islamic educational institution, has a strategic role in shaping the character of the Islamic young generation. Pesantren not only teaches religious knowledge, but also instills moral and spiritual values to its students. There is a typical pesantren education management that can be applied to the younger generation, namely; 1) Direction 2) Training 3) Assignment 4) Habituation 5) Supervision 6) Uswah Hasanah. There are six main points of typical pesantren management that can be used as a form of effort in character building in the Islamic young generation so that it can be more directed and totality. In this research, the author uses a qualitative method with the approach used is descriptive analysis, namely, retelling what has been seen and researched by researchers. So that the results obtained show that the cultivation of the pesantren education management system in pesantren produces sustainable positive habits in students so that they are able to present Long Life Education in the students' personalities even though they are no longer living in the pesantren environment.